ETHICAL CHALLENGES IN HEALTHCARE ARISING FROM THE COVID-19 PANDEMIC - Fernandes, Anthony L. (Asian Horizons, 2020)
The COVID-19 pandemic has, till the end of September 2020, infected more than 34 million people the world over, and more than one million have died. The ethical challenges it has raised are many. This article highlights some of the main ethical challenges in healthcare. It argues that the pandemic could have been avoided, or, at best, very much reduced, if the problem had been nipped in the bud, and due warnings were sounded to other countries; the role of China and the WHO are particularly highlighted. Denial of the problem, and inaction by some prominent world leaders who placed politics and economics before health, has resulted in their countries being most affected by the pandemic. The article also discusses some of the other ethical concerns in healthcare that have arisen: the problems of triage; the effect on non-COVID related medical care; problems of honouring the requirements of informed consent, CPR, DNR Orders, etc.; the sad plight of healthcare and other frontline workers; the issue of citizens’ privacy and rights; the ethics of human challenge studies, and problems in developing and distributing a safe and effective vaccine. The important values of human dignity, human rights, privacy, equity, and justice are to be upheld at all times as we make our way out of this crisis. A close collaboration between all the principal actors as well as the citizens of the world is necessary to help end the pandemic and to return to normalcy.